Sumber Makna Hidup bagi Narapidana di Lapas Klas IIA Banda Aceh - Rika Dewi (Jurnal Sosiologi Agama Indonesia (JSAI), 2020)
This article aims to find out the various sources of life meaningful life of Class IIA Banda Aceh prisoners studied based on the sources of meaningful life expressed by Bastaman (2007), namely Creative Values ​​(creative values), Experiential values ​​, and Atituditional values. Values ​​(attitude values). The population of class II prisoners as many as 488 samples in this study, so the researcher took a sample of 50 prisoners using purposive random sampling. Data retrieval using questionnaires in the form of a Likert scale. The results showed that the highest value of the source of the meaning of life is the source of creative values ​​with a mean of 46.32 meaning that prisoners will still have the meaning of life when they can work, work, create, and carry out their duties and obligations as well as possible with full responsibility. While the lowest value is Experiential Value with a mean value of 34.40 which means that the prisoner feels happy and will have the meaning of life with the religious values ​​given in the LP, such as still having hope to live and trying to be the best person after leaving the LP. Then they also want to learn to read the Al-Quran, so that on average they can read the Al-Qur'an. In obtaining the sources of a meaningful life, there are different results for each prisoner. This means that the sources of meaningful life can be obtained through the experiences of different individuals. This is also related to age and marital status (such as married or unmarried)